An Examination of a Few Antecedents of Environmental Sustainability Using Structural Equation Modelling - Adow, Anass Hamad Elneel; Safeer, M. M.; Ibrahim, Rufida Gamr Eldoula Moahmed; Alam, M. Syeed (International Journal of Energy Economics and Policy, 2024)
Awareness of environmental issues and appropriate knowledge about solving them through "scalable acts and behaviours" help engage and contribute to environmental sustainability. Though there exist volumes of literature on green behaviours, there is a lack of literature on what motivates sustainable behaviour. The present study bridges this research gap by identifying green shared vision (GSV) and green value (GV) as antecedents of perceived environmental sustainability. The study is based on data collected from 384 respondents among gainfully employed samples from Saudi Arabia. The study used structural equation modeling (SEM) to analyze the data. The findings show significant positive relationships between the variables, supporting the proposed model. The study has significant implications for sustainability and administrators, suggesting the need to improve strategies related to green behaviour.